The Utility of Ocular Imaging in Traumatic Optic Nerve Avulsion: A Case Report - ikhwanuliman Putera; Syntia Nusanti; Nur Aisyah Rahmawati; Annisa Nindiana Pertiwi; Mario Marbungaran Hutapea (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Objective: To describe a detailed presentation and the utility of ocular imaging, both ocular ultrasound and orbital computed tomography (CT), to confirm the diagnosis of traumatic ONA in which megadose steroid would give no advantage. Case Presentation: A five-year-old boy came with a unilateral sudden visual loss after incidentally falling with his left eye struck to a handlebar of a parked bicycle. His left eye had no light perception, ophthalmoplegia, and showing 4+ relative afferent pupillary defect. A hallmark